The reality of the management of the administrative and technical crisis of the members of the bodies of some of the sport unions in Baghdad - Mousa Jawad, Sundus; Raad Ibrahim, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Crisis management becomes successful if you have successful leadership skills. It is important to avoid the administrative crisis of members because it helps to give job security and coordination between attention to administrative values and their application to achieve the goals of the institution. Provide information on the administrative and technical crisis that helps to overcome it. Attention to leadership skills in all institutions because it is the basis of successful administrative work. Doing a number of research management because it is a fundamental principle of the growth of the institution. We advise developing work to create courses on how to overcome crises on both sides.